The Effect Of Team Quiz Assistant Method Of Question Card Medion Mathematics Learning Outcomes - Balgis Riski Ramadhani (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
This study aims to determine the effect of the team quiz method with the help of questioncard media on the mathematics learning outcomes of third grade students at SD Negeri Gondosuli 1, Muntilan District. This study uses a quantitative approach with a pre-experimental design type one group pretest posttest design with a total sample of 19 students who received treatment in the form of a team quiz method assisted by a questioncard media. Data collection techniques in the form of tests (pretest and posttest) to revealstudent learning outcomes and observation sheets to reveal the implementation of theteam quiz method. Validity test using Product Moment correlation with valid results of thepretest 29 items and the posttest 32 items. The reliability test used Chronbach's Alphawith the results on the pretest 0.963 and the posttest 0.962. The data analysis techniquein this study used the Kolmogorov-Smirnov analysis prerequisite test and showed a resultof 0.200 on the pretest and 0.129 on the posttest. Hypothesis testing using Paired samplet-test. The results of this study indicate that there is an increase in the average pretestand posttest results before and after being given treatment using the team quiz methodwith the help of question card media. The average pretest value before treatment was 62while the posttest value after treatment was 79. The results of the analysis of the Pairedsample t-test test showed a significance value of 0.001 (less than 0.05). So it can beconcluded that the team quiz method with the help of question card media hasan effect on mathematics learning outcomes.